Miniature Media Characterized by Ethnomathematics in Improving Mathematics Abilities for Third Grade Elementary Schools - Lestari, Desak Ketut Trisna; Suarjana, I Made; Paramita, Made Vina Arie (Universitas Pendidikan Ganesha, 2023)
The low interest during the learning process of Mathematics in elementary schools’ results in decreased student learning outcomes, moreover the use of inappropriate learning methods which generally only focus students on practicing problems certainly makes students quickly feel bored and consider Mathematics not a fun lesson. Learning and student learning outcomes in Mathematics are influenced by several factors, including learning media. Learning media that is designed to be interesting and in accordance with the needs and characteristics of students can affect student attention to be active in the learning process, moreover Mathematics is closely related to everyday life, especially those related to calculations (addition, subtraction, multiplication and division). The purpose of this study was to analyze the validity of miniature media characterized by ethnomathematics, analyze the practicality of miniature media characterized by ethnomathematics and analyze the effectiveness of miniature media characterized by ethnomathematics in improving the ability to understand flat building material for grade III elementary school students. This development research uses a one group pre-test post-test design. The subjects in this study consisted of 1 media expert, 1 material expert, 1 practitioner, and 13 third grade elementary school students. The results were analyzed using descriptive statistics and the hypothesis was tested using the correlated t-test technique. The results showed that the miniature media characterized by ethnomathematics was valid, practical and effective in improving the ability to understand flat shape material for third grade elementary school students.